2023
DOI: 10.1101/2023.09.07.556668
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-scale phenotypic and genomic characterization ofListeria monocytogenessusceptibility to quaternary ammonium compounds

Mirena Ivanova,
Martin Laage Kragh,
Judit Szarvas
et al.

Abstract: Listeria monocytogenesis a significant concern for the food industry due to its ability to persist in the food processing environment. Decreased susceptibility to disinfectants is one of the factors that contribute to the persistence ofL. monocytogenes. The objective of this study was to explore the diversity ofL. monocytogenessusceptibility to quaternary ammonium compounds (QACs) using 1,671L. monocytogenesisolates. This was used to determine the phenotype-genotype concordance and characterize genomes of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Recent studies have observed great concordance (up to 99%) between known QAC resistance genes and tolerant/sensitive phenotypes, raising the question of the benefit of a more complex ML solution [10]. In this dataset, 20 isolates showed tolerance to BC in laboratory experiments, but no QAC resistance genes were observed.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Recent studies have observed great concordance (up to 99%) between known QAC resistance genes and tolerant/sensitive phenotypes, raising the question of the benefit of a more complex ML solution [10]. In this dataset, 20 isolates showed tolerance to BC in laboratory experiments, but no QAC resistance genes were observed.…”
Section: Discussionmentioning
confidence: 96%
“…To be able to compare the classification predictions from our trained model with the validation set, we categorised the MIC values into tolerant and sensitive groups (i.e., phenotypes). This has been done as described by Ivanova et al [10]. In short, for the publications that do not report an MIC cut-off for tolerant/sensitive separation, we screened all isolates for the presence of one of four genes associated with QAC resistance (qacH (multiple variants), bcrABC (JX023284.1), emrE (NC_013766.2:c1850670-1850347), and emrC (MT912503.1:2384-2770)).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The L. monocytogenes isolates for the benchmarking data set 1 (n=97) were selected from Ivanova et al (2023) [28] and cover a broad range of geographical regions, isolation sources and isolate sub-types. The isolates' short-read WGS data was acquired from the European Nucleotide Archive (ENA).…”
Section: Benchmarking Data Setmentioning
confidence: 99%